IKONISASI PAKAIAN ‘ISLAMI’: BENTUK KOMUNIKASI NON VERBAL DI LINGKUNGAN PERGURUAN TINGGI ISLAM - Zafirah Quroatun Uyun (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2020)
Abstract: Iconization in an institution, especially for university there are some consequences. In addition to influencing visions and missions, lifestyles, religions, even cultural industry provides its own style. As with 'Islamic' clothing in several Islamic universities that begin to process into an icon due to negotiation of religious and cultural values, communication patterns change from just talking, writing and discourse to a form of non-verbal communication which is contains codes and symbols. This research tries to elaborate 'Islamic' clothing iconization forms by describing a set of codes and symbols of non-verbal communication using 'Islamic' clothing. Analysis of the influence of lifestyle, religion, customs will be described using the method of literature and observation. This research found that the intersection between industrialization of culture, lifestyle and religion with non-verbal communication had consequences for iconization.